2022
DOI: 10.3389/fpls.2021.772644
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Efficiency of Photosystem II in Inverted Leaves of Soybean [Glycine max (L.) Merr.] Affected by Elevated Temperature and High Light

Abstract: In summer, high light and elevated temperature are the most common abiotic stresses. The frequent occurrence of monsoon exposes the abaxial surface of soybean [Glycine max (L.) Merr.] leaves to direct solar radiation, resulting in irreversible damage to plant photosynthesis. In this study, chlorophyll a fluorescence was used to evaluate the functional status of photosystem II (PSII) in inverted leaves under elevated temperature and high light. In two consecutive growing seasons, we tested the fluorescence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…Accordingly, heat stress treatment significantly decreased the leaf net photosynthesis rate and plant biomass during the recovery stage (Figure 5). These results were consistent with the previous studies that determined that heat stress significantly increased ROS levels and decreased the photosynthetic capacity and grain yield [36][37][38]. Although the activity of antioxidant enzymes (SOD, CAT, and POD) and contents of antioxidant substances (ASA and GSH) were enhanced, the accumulation level of ROS was still significantly increased under heat stress, suggesting that the production rate of ROS under heat stress exceeded its clear rate in this study.…”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, heat stress treatment significantly decreased the leaf net photosynthesis rate and plant biomass during the recovery stage (Figure 5). These results were consistent with the previous studies that determined that heat stress significantly increased ROS levels and decreased the photosynthetic capacity and grain yield [36][37][38]. Although the activity of antioxidant enzymes (SOD, CAT, and POD) and contents of antioxidant substances (ASA and GSH) were enhanced, the accumulation level of ROS was still significantly increased under heat stress, suggesting that the production rate of ROS under heat stress exceeded its clear rate in this study.…”
Section: Discussionsupporting
confidence: 93%
“…The increase in F v /F m indicates the increase in photochemical efficiency of photosystem II (Guidi et al, 2019). Plants absorb blue and red-light spectra more than green and yellow light spectra (Wang et al, 2022). Different absorption for different lights may partially explain the difference in CO 2 absorption of plants growing under different light spectra (Aalifar et al, 2020a;Aalifar et al, 2020b;Javadi Asayesh et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The application of MT improved yield-related characteristics such as seed yield per plant, 1000 seed weight, seed oil content, and seed yield in mustard [122]. Wang et al [123] investigated the impact of MT on yield traits of soybean and reported an increased number of pods, seeds per pod, and grain yield under stress. In cucumber, the number of fruits, fruit weight, and total yield of the plant were increased under osmotic stress in response to MT treatment [124].…”
Section: Melatonin's Role In Crop Yield and Qualitymentioning
confidence: 99%